IDADE DA MENOPAUSA E DA MENARCA: inquérito populacional em mulheres climatéricas - Sousa, Ana Cleide Vasconcelos de (2012)
A woman runs during successive steps biological life that reflect your "genital evolution‖. These periods are marked by wide variations distinct with menarche, understood as the mark of adolescent maturation, and menopause which corresponds to the end of their reproductive capacity. The objective of this study was to relate in perimenopausal women with menopausal age the determining factors for its occurrence. This is a transversal study, obtained from a population-based survey. This is a transversal study, obtained from a population-based survey. Were selected through cluster sampling, 1209 women living in São Luis - MA, aged 45 years and older, from April to July 2008. The questionnaire was the instrument used in household interviews. For data analysis, we used Stata statistical package, version 10.0 and to assess the homogeneity between the groups we used the Pearson chi-square test. It was observed that prevailed women aged 50 to 59 years (53.9%), brown in color (46.9%), schooling 9-12 years of education (56.7%), with partner (55.9%), unemployed (46%) and belonging to economy class C (51.1%). The mean age for menarche was 13.4 years, for natural menopause was 46.9 years and the duration of reproductive age was 33.6 years. The duration of reproductive age, regardless of age at menarche had no statistically significant difference between women.